The Use of Three-Monthly Injectable Contraceptives with the Incidence of Aminorhae and Weight Change in Family Planning Acceptors at the Birthing Practices of Midwife Wulan Mardikaningtyas - Mohammad Rizqi; Sulastri Sulastri (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Hormonal contraceptives, especially injectable Depo Medroxy Progesterone Acetate (DMPA), are the most popular among family planning advocates. Although it may cause changes in weight and menstrual cycle or amenorrhea, Depo Medroxy Progesterone Acetate is effective in preventing pregnancy. The purpose of this study is to ascertain how women's weight fluctuations and the usage of injectable family planning for three months are related to amenorrhea. Cross-sectional research design and quantitative research were employed in this study. This study was carried out at Wulan Mardikaningtyas Independent Practice Midwife in May and July of 2024. There were 46 users of injectable contraceptives for three months at Wulan Mardikaningtyas Midwife Independent Practice who made up the study's population. Total sampling is the method used for sampling. gathering information with a questionnaire. employing the chi-square test in bivariate analysis of the data. According to the study's findings, women who actively used injectable Depo Medroxy Progesterone Acetate contraceptives saw a rise in amenorrhea and an increase in body weight within three months. So the conclusion of this study is that there is a relationship between the use of Depo Medroxy Progesterone Acetate injectable contraceptives for three months with the incidence of amenorrhea and weight changes in three-month injectable birth control acceptors (p-value=0.015). The importance of monitoring hormonal side effects in injectable contraceptive users, as well as providing adequate information to prospective users regarding potential changes in menstrual cycles and body weight. Keywords: Amenorrhea, Depo Medroxy Progesterone Acetate, Hormones progesterone & estrogen, Weight Gain